Revolutionizing language learning: Integrating generative AI for enhanced language proficiency - Yeh, Hui-Chin (Educational Technology ＆ Society, 2024)
This paper presents the integration of generative artificial intelligence (GAI) and other AI tools in English as a Foreign Language (EFL) education, addressing the limitations of traditional pedagogical approaches. Conventional EFL methods, often reliant on rote learning for standardized tests, struggle to impart practical language skills relevant to real-world scenarios. By leveraging AI technologies, this study proposes innovative solutions to these challenges, creating authentic, context-rich learning environments and facilitating creative integration of technology for language acquisition. The synergy between GAI and other technology tools enables the creation of immersive language scenarios, offering tailored exercises and narratives that cater to individual proficiency levels and learning objectives. This collaborative approach empowers both teachers and learners to generate their own content, thereby enhancing comprehension and confidence across diverse linguistic contexts. By transcending traditional teaching methods, the integration of GAI with other tools emerges as a transformative catalyst in language education, providing learners with authentic language practice opportunities and empowering them to engage with English in innovative and personalized ways. The paper concludes by urging EFL educators to embrace AI not merely as supplementary resources but as integral components in redefining pedagogical strategies, ensuring the development of more engaging, tailored, and effective language learning environments.